Investigation of Prospective Teachers' Use of Mobile Technologies in Teaching Activities - Sapanca, Hamza Fatih; Kaya, Omer Sami; Taspolat, Ata; Tezer, Murat (Assoc Development Science Engineering & Education, 2022)
The purpose of this research is to examine the pre-service teachers' use of mobile technologies in teaching activities. In this study, the survey method, one of the research methods, was used. The 199 prospective teachers studying at the Faculty of Education, a private university in Northern Cyprus, were included in the workgroup of the research. The 5-point Likert-type scales were used to measure the frequencies of using mobile technologies in instructional activities, motivation, and attitudes towards mobile technologies, competencies in mobile technology use, and its social effects. It was found that social factors had the lowest effect on the use of mobile technologies. Additionally, no gender-based difference was found in the mobile use frequency, motivation, attitude, competency, and social impact of prospective teachers. Moreover, the frequency, motivation, attitudes, competency, and social impact levels of students from the Department of Computer and Instructional Technologies are significantly higher than those departments from Guidance and Psychological Counselling, Special Education, Music Teaching, Elementary School Mathematics Teacher Education, Department of Pre-School Teaching, Classroom Teaching Department, Social Sciences Teacher Education, Turkish Language Teaching. It was concluded that having problems for mobile learning activities that can be used in the scope of mobile learning significantly influences the frequency of use, motivation, attitude, competency, and social impact of the students. Along with this, it was found that the following factors, given in order of importance, are influential on the frequency of the use of mobile technologies by prospective teachers in instructional activities: motivation, attitude, competency, and social impact.
Keywords: prospective teachers; mobile technologies; learning activities; pre-services teachers